Broadening the Applicability of a Custom Multi-Platform Panel of Microhaplotypes: Bio-Geographical Ancestry Inference and Expanded Reference Data - de la Puente, María; Ruiz-Ramírez, Jorge; Ambroa-Conde, Adrián; Xavier, Catarina; Amigo, Jorge; Casares de Cal, María Ángeles; Gómez-Tato, Antonio; Carracedo, Ángel; Parson, Walther; Phillips, Christopher; Lareu, María Victoria (Frontiers in Genetics, 2020)
The development of microhaplotype panels for massively parallel sequencing platforms is gaining increasing relevance for forensic analysis. Here, we expand the applicability of a 102 autosomal and 11 X-chromosome panel of microhaplotypes, previously validated with both MiSeq and Ion S5 massively parallel sequencing platforms and designed for identification purposes. We have broadened reference population data for identification purposes, including data from 240 HGDP-CEPH individuals of native populations from North Africa, the Middle East, Oceania and America. Using the enhanced population data, the panel was evaluated as a marker set for bio-geographical ancestry (BGA) inference, providing a clear differentiation of the five main continental groups of Africa, Europe, East Asia, Native America and Oceania. An informative degree of differentiation was also achieved for the population variation encompassing North Africa, Middle East, Europe, South Asia and East Asia. In addition, we explored the potential for individual BGA inference from simple mixed DNA, by simulation of mixed profiles followed by deconvolution of mixture components.